Biomarkers of Body Composition - Chang, Connie Y.; Lenchik, Leon; Blankemeier, Louis; Chaudhari, Akshay S.; Boutin, Robert D. (Seminars in Musculoskeletal Radiology, 2024)
The importance and impact of imaging biomarkers has been increasing over the past few decades. We review the relevant clinical and imaging terminology needed to understand the clinical and research applications of body composition. Imaging biomarkers of bone, muscle, and fat tissues obtained with dual-energy X-ray absorptiometry, computed tomography, magnetic resonance imaging, and ultrasonography are described.
Keywords: adipose tissue; osteoporosis; obesity; myosteatosis; sarcopenia